2006
DOI: 10.1073/pnas.0505663103
|View full text |Cite
|
Sign up to set email alerts
|

Reveromycin A, an agent for osteoporosis, inhibits bone resorption by inducing apoptosis specifically in osteoclasts

Abstract: Mature bone-resorbing osteoclasts (OCs) mediate excessive bone loss seen in several bone disorders, including osteoporosis. Here, we showed that reveromycin A (RM-A), a small natural product with three carboxylic groups in its structure, induced apoptosis specifically in OCs, but not in OC progenitors, nonfunctional osteoclasts, or osteoblasts. RM-A inhibited protein synthesis in OCs by selectively blocking enzymatic activity of isoleucyl-tRNA synthetase. The proapoptotic effect of RM-A was inhibited by neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 33 publications
4
83
0
Order By: Relevance
“…As a result, and in direct contrast to its antitumor activity in vitro and in a s.c. xenograft model, 17-AAG indirectly stimulates the intraosseous growth of PC-3M prostate cancer cells. However, this can be counteracted by three mechanistically distinct inhibitors of osteoclastogenesis, a Src kinase inhibitor (23), a bisphosphonate (24), and the osteoclast-specific apoptosis inducer reveromycin A (25). This study emphasizes the importance of obtaining a more complete understanding of the complex role played by Hsp90 in regulating normal tissue homeostasis, and how these events impact tumor growth and response to targeted therapy.…”
mentioning
confidence: 99%
“…As a result, and in direct contrast to its antitumor activity in vitro and in a s.c. xenograft model, 17-AAG indirectly stimulates the intraosseous growth of PC-3M prostate cancer cells. However, this can be counteracted by three mechanistically distinct inhibitors of osteoclastogenesis, a Src kinase inhibitor (23), a bisphosphonate (24), and the osteoclast-specific apoptosis inducer reveromycin A (25). This study emphasizes the importance of obtaining a more complete understanding of the complex role played by Hsp90 in regulating normal tissue homeostasis, and how these events impact tumor growth and response to targeted therapy.…”
mentioning
confidence: 99%
“…We recently found a unique biological activity: RM-A-induced cell death occurred specifically in osteoclasts with a several hundred-fold lesser concentration of RM-A than that which inhibited the cell growth of various other cells, including osteoblastic cells and osteoclast precursor cells. (43) It is unlikely that such selectivity is due to the target molecule of RM-A. Chemical analysis of RM-A showed that it is an acidic compound with three carboxylic groups in its structure (Fig.…”
Section: Small Molecules That Selectively Inhibit Osteoclast Functionmentioning
confidence: 99%
“…CAII, carbonic anhydrase II; Cath K, cathepsin K; M-CSF, macrophage-colony stimulating factor; MMP-9, matrix metalloproteinase-9; PDGF, platelet-derived growth factor. (9) Alendronate, Zoledronate FPP synthase Marketed (9) MK-0822, AAE581 Cathepsin K Clinical (12) AZD0530, CGP76030 c-Src Clinical, Preclinical (19) L-000845704, SB265123 a V b 3 integrin Clinical, Preclinical (23,57) FR202126, Iejimalide A, B V-ATPase Preclinical (26,30) NS3736 ClC-7 Cl ) channel Preclinical (32) KN-93 CaMKIV Preclinical (33) LFM-A13 Btk ⁄ Tec Preclinical (34) (-)-DHMEQ, PDTC NF-jB Preclinical (35,36) Reveromycin A IleRS Preclinical (43,44) CaMKIV, Ca 2+ ⁄ calmodulin-dependent kinase IV; (-)-DHMEQ, (-)-dehydroxymethylepoxyquinomicin; FPP, farnesyl pyrophosphate; IleRS, isoleucyl-tRNA synthetase; PDTC, pyrrolidine dithiocarbamate.…”
Section: Small Molecules That Selectively Inhibit Osteoclast Functionmentioning
confidence: 99%
“…Reveromycin A (RM-A) 3 (3), which is a spiroacetal polyketide compound produced by Streptomyces sp. SN-593, inhibits bone resorption by specifically inducing apoptosis in osteoclasts (4). It has been demonstrated that RM-A inhibited bone metastasis of lung and prostate cancer cells through anti-osteoclastic activity (5-7).…”
mentioning
confidence: 99%